Vulnerabilidade socioambiental e a perspectiva de resiliência a desastres nas cidades da Região Nordeste do Brasil: João Pessoa, Recife e Maceió - Morais, Palloma Damascena (2020)
Population growth, inadequate occupation, lack of basic assistance, and above all, the lack of urban planning in the cities, have contributed to many problems in the scope of environmental management. Mainly in developing countries, such as Brazil, thus enhancing the risks to disasters related to natural phenomena. Therefore, the importance of analyzing climatic events together with vulnerability, this research sought to evaluate resilience to disasters related to natural phenomena from the socio-environmental vulnerability in the cities of João Pessoa, Recife and Maceió located in the Northeast of Brazil. The present study was guided by the Campaign “Making Cities Resilient - My City is getting ready!” originated by the United Nations Office for Disaster Reduction - UNISDR. The quantitative and adapted approach methodology, for determining vulnerability indexes to disasters related to natural phenomena, according to the variable components of three indicators was used: Exposure, Sensitivity and Adaptive Capacity. From the preliminary study of all the Northeastern capitals, the vulnerability indexes of the cities of João Pessoa, Recife and Maceió were selected for the analysis of this work. Social, economic, infrastructural data and areas susceptible to disasters were used, mainly available on websites and official reports from government agencies. It was found that the city of Recife is the most vulnerable, with the index of 0.611, followed by Maceió city with the value of 0.568, and João Pessoa city presented a value of 0.508 of the vulnerability index. Although Recife city has the largest number of areas prone to disasters risk by mass movement (landslide), in general, Maceió city proved to be the most exposed to disasters and rainfall. The João Pessoa city mostly presented the best results for the three indicators evaluated. However, it was observed that all municipal managers needs to formulate public policies for the preparation of local plans for disaster preparedness and mitigation, thus, the Campaign “Making Cities Resilient - My city is getting ready!” is an incentive tool in the search disaster reduction and the achievement of resilience.